Vascular Grafting Strategies in Coronary Intervention - Knight, Darryl K.; Gillies, Elizabeth R.; Mequanint, Kibret (Frontiers in Materials, 2014)
With the growing need for coronary revascularizations globally, several strategies to restore blood flow to the heart have been explored. Bypassing the atherosclerotic coronary arteries with autologous grafts, synthetic prostheses and tissue-engineered vascular grafts continue to be evaluated in search of a readily available vascular graft with clinically acceptable outcomes. The development of such a vascular graft including tissue engineering approaches both in situ and in vitro is herein reviewed, facilitating a detailed comparison on the role of seeded cells in vascular graft patency.